Nonorganic Vision Loss in Ophthalmic Practice: Diagnostic Frameworks, Differential Considerations, and Evidence-Based Management - Alhunishi, Suleman Abdu; Bashayr Mousa Mohammed Ageeli; Maram Hussin Mohammed Banajiah; Mohammed Obaid A Alanazi; Ashwaq Rabea Alabeeri; Fahad Abdullah Alahmadi; Wafaa Mohammed Alharbi; Omar Nafel Alharbi; Shujaa Murdhi Alrasheedi; Khalid Khlil Galfan Kamli; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Nonorganic vision loss (NOVL), also termed functional or psychogenic vision loss, represents visual impairment without sufficient structural or physiological pathology to explain the reported deficit. It poses diagnostic and management challenges due to its heterogeneous presentation and overlap with organic and psychiatric conditions. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the diagnostic frameworks, differential considerations, and evidence-based management strategies for NOVL in ophthalmic practice. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature-based synthesis was conducted, integrating ophthalmic, neuro-ophthalmic, and psychosocial perspectives. The review emphasizes systematic evaluation, exclusion of organic disease, and multidisciplinary management principles. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NOVL accounts for a clinically significant proportion of vision loss presentations across age groups, with prevalence estimates ranging from 16% in adults with ocular motor disorders to nearly 50% in pediatric cohorts. Etiology is multifactorial, involving psychogenic mechanisms (conversion disorder), symptom amplification, trauma-related pathways, and sociocultural influences. Diagnostic hallmarks include discordance between subjective complaints and objective findings, preserved automatic visual responses, and physiologically implausible patterns on visual field testing. Management centers on empathetic reassurance, patient education, and psychological referral, with cognitive-behavioral therapy and structured follow-up improving outcomes. Prognosis is generally favorable when NOVL is recognized early and addressed through a biopsychosocial approach. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NOVL is a genuine and disabling condition requiring careful exclusion of organic pathology, sensitive communication, and integrated care. Early recognition and multidisciplinary intervention reduce unnecessary investigations, mitigate distress, and support functional recovery.